2015
DOI: 10.28945/2089
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Graduate Students’ Attitudes towards Team Research and Their Scholarly Productivity: A Survey Guided by the Theory of Planned Behavior

Abstract: This study explores the attitudinal and motivational factors underlying graduate students’ attitudes towards team research. Guided by the Theory of Planned Behavior, we hypothesize that attitude, subjective norm, and perceived behavioral control are three major determinants of graduate students’ intentions to conduct team research. An instrument was developed to measure the influences of these factors on students’ intentions and relevant scholarly productivity. A total of 281 graduate students from a large,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…The results from this study supported prior research on the importance of psychological factors such as social presence (Gunawardena & Zittle, 1997;Short et al, 1976), research self-efficacy (Coryell & Murray, 2014;Wei et al, 2015), isolation (Golde & Dore, 2001;Hawlery, 2003;Lovitts, 2001), and intrinsic motivation (Deci & Ryan, 2000;Gardner, 2010) to improve doctoral student success. The findings of the current study indicated that social presence enabled research self-efficacy, reduced isolation, and contributed to intrinsic motivation.…”
Section: Case Study Summary: a Visual Model Of Th E Phenomenonsupporting
confidence: 85%
See 2 more Smart Citations
“…The results from this study supported prior research on the importance of psychological factors such as social presence (Gunawardena & Zittle, 1997;Short et al, 1976), research self-efficacy (Coryell & Murray, 2014;Wei et al, 2015), isolation (Golde & Dore, 2001;Hawlery, 2003;Lovitts, 2001), and intrinsic motivation (Deci & Ryan, 2000;Gardner, 2010) to improve doctoral student success. The findings of the current study indicated that social presence enabled research self-efficacy, reduced isolation, and contributed to intrinsic motivation.…”
Section: Case Study Summary: a Visual Model Of Th E Phenomenonsupporting
confidence: 85%
“…Various psychological factors including social presence (Gunawardena & Zittle, 1997;Short et al, 1976), research self-efficacy (Coryell & Murray, 2014;Wei et al, 2015 ), isolation (Golde & Dore, 2001;Hawlery, 2003;Lovitts, 2001), and intrinsic motivation (Deci & Ryan, 2000;Gardner & Gopaul, 2012), influence retention of doctoral students. The purpose of this article was to share the experience of one university that implemented an emerging global cloud-based video technology for dissertation chairs to coach and mentor online doctoral students during their dissertation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ajzen (1985) then proposed the TPB, introducing perceived behavioural control (PBC) into the TRA model. The TPB has its roots in the expectancy-value framework (Ajzen & Fishbein, 1980), which posits that one's motivation to perform a behaviour is a result of both the expectation of a specified outcome and the perceived value of those outcomes (Wei et al, 2015). Ajzen (1985) went a step beyond the expectancy-value account and incorporated the component of PBC into the TPB, which is most compatible with perceived self-efficacy (SE) in the social cognitive theory.…”
Section: Decomposed Theory Of Planned Behaviourmentioning
confidence: 99%